Prove di comprensione del testo: dalla somministrazione alla revisione - Marika Calenda; Concetta Ferrantino; Anna Maria Petolicchio (LED Edizioni Universitarie, 2020)
The paper describes the review procedure for a reading comprehension test designed for high school students. The objective is to analyze the functioning of a measuring instrument, used in the context of an investigation on reading in the high schools of three Italian regions - Basilicata, Calabria and Campania - in order to improve and perfect this instrument in view of the subsequent research phases. The reflections that follow are intended to provide a guide for the interpretation of the response frequencies, the indices of discrimination and difficulty, useful for establishing which questions need further revision. By analyzing internal consistency, construct validity, understood as item discriminativity, difficulty, biserial point values and distribution of answers on the four options provided by the multiple answer, we intend to demonstrate how, by administering the same test several times, we they can obtain new indications that allow them to file and refine the problematic questions, reflecting on the critical issues that have emerged (Agrusti, 2008).